German history from the margins - Gregor, Neil, 1969-; Roemer, Nils H.; Roseman, Mark (Indiana University Press, 2006)
German History from the Margins offers new ways of thinking about ethnic and religious minorities and other outsiders in modern German history. Many established paradigms of German history are challenged by the contributors' new and often provocative findings, including evidence of the striking cosmopolitanism of Germany's 19th-century eastern border communities; German Jewry's sophisticated appropriation of the discourse of tribe and race; the unexpected absence of antisemitism in Weimar's campaign against smut; the Nazi's embrace of purportedly "Jewish" sexual behavior; and post-war Germany